Developmental plasticity associated with early structural integration and evolutionary patterns: Examples of developmental bias and developmental facilitation in the skeletal system. Issue 1 (14th October 2019) - Kavanagh, Kathryn
Abstract: The relation of developmental plasticity to evolutionary diversification is a key component of evolutionary theory involving developmental bias, but the basis of the relationship varies among traits and among taxa. Here I review some scenarios of how structural integration during early organogenesis could influence this relationship. When condensations are highly integrated and dependent on each other during early organogenesis, both plasticity and evolution are restricted, for example size proportions in molar tooth rows and phalanges within a digit. When similar condensations develop and remain separate (in tracheal cartilages and feather buds), they show high levels of variation and diversity in number but not in shape and size, at least at early stages. When non‐similar structures form separately and then integrate while still undergoing patterning, high levels of plasticity (in number, size, shape; in rib uncinate processes) or new dimensions of ecologically‐significant variation (cusp offset, in mammal teeth) are seen. Although each of these structural integration scenarios is unique, the modulation of evolvability is detectable and informative. Parsing the influence of structural integration at these developmental levels, rather than later‐stage structural correlations or only through genetic covariation, may be necessary to advance understanding of evolvability of the phenotype. Abstract : Structural integration among parts of a developing embryo may help explain how easily organs or bones can evolve new features, but an examination of several different systems shows that the pattern goes against theoretical expectations. The most developmentally plastic and evolutionarily diverse systems come from integration among nonhomologous structures.